Reportar e afetar (-se): atos de objetivação e subjetivação na grande narrativa impressa “viúvas do veneno” - Araújo, Mayara Carolinne Beserra de (2019)
The operation of the concepts of subjectivity and objectivity in journalism is embedded in a profuse context of economic, social, technological and paradigmatic transformations (still in progress) (CHARRON, BONVILLE, 2016, MARCONDES FILHO, 2000, MEDINA, 2014, DEUZE, 2015; ), resulting in multiple forms of apprehension of the reality. Considering this context, the present study analyzes the place of subjectivation and objectification in the special report “Viúvas do Veneno” (Widows of Venom), produced by the journalist Melquíades Júnior, from the Diário do Nordeste – originated so in a conventional and hegemonic place (FAIRCLOUGH, MIGUEL; BIROLI, 2010) and from the interaction of several narrators: newspaper, journalist and sources (MOTTA, 2013). We try, from this research, to understand how the interaction between objectification and subjectivation is revealed in the text and in the productive routines of the reporter. To do so, we build a specific method, entitled (just for didactic purposes) Analysis of Acts of Objectivation and Subjectivation in Journalism (Anatos), based mainly on Critical Narrative Analysis (MOTTA, 2013) and Critical Discourse Analysis (FAIRCLOUGH, 2016). We find that, instead of a strictly oppositional relationship, subjectivity and objectivity can develop complementarities, pointing to a complex journalism (MORIN, 2007).